Study On Physical Layer Wireless Security Techniques - Lemya, S; Meera, VM; Thrupthi, A (International Journal of Computer Sciences and Engineering, 2025)
Communication security is an essential and progressively difficult issue in wireless networks. Physical-layer approach to secret key generation which is each quick and independent of channel variations is taken into account. This approach makes a receiver jam the signal during a manner that also permits it to decrypt the info, nevertheless prevents alternative nodes from cryptography. Another well-known approach for achieving information-theoretic secrecy depends on deploying artificial noises to blind the intruders’ interception within the physical layer. A multiple inter-symbol obfuscation (MIO) theme is planned, that utilizes a collection of artificial vociferous symbols to alter the initial knowledge symbols within the physical layer. MIO will effectively enhance the wireless communications security.